Money, money, money; what do trainers and rocking horses have to do with it? - Harrocks, Rebecca (Practical theology, 2025)
This theological reflection explores what principles should underpin a theology of possessions given their close and often inextricable relationship to money. It intends to address some of the nuanced and conflicting emotions that possessions can arouse, as documented on the Preachersnsneakers Instagram page and The Repair Shop television programme, and it situates these in a context of apparent disapproval of material possessions that can be found in some oft-cited biblical verses and the associated literature, which often fails to acknowledge that possessions can also be beneficial and evoke positive feelings. Using the Killen and de Beer method of theological reflection in conversation with Christian Scripture and the Franciscan Tradition, as well as drawing on the scholarship of others in the field, this reflection proposes some guiding principles with which possessions (and money) should be regarded by those trying to live a Christian faith. The conclusion is a brief theology of possessions underpinned by proposed principles of stewardship, divine ownership, spiritual dangers, self-discipline, and ‘correct’ attitude.